On coincidence points of generalized contractive pair mappings in convex metric spaces - Moohammad Moosaei; Azizollah Azizi (Journal of Hyperstructures)
We obtain a contractive condition for the existence of coincidence points of a pair of self-mappings defined on a nonempty subset of a complete convex metric space. Moreover, we show that weakly compatible pairs have at least a common fixed point.